Effectiveness of ECMO treatment for acute respiratory distress syndrome of patients with covid-19: a literature review - Reis, Leticia Serbosa (2024)
Introduction: The highly virulent SARS-CoV-2 virus spread worldwide between 2020 and 2022, causing the covid-19 pandemic. The characteristics of easy transmission, difficulty to control, and severe respiratory conditions led to social isolation and the use of FFP2 masks, with hospitalizations and high mortality. Treatments such as medications, patient pronation, and invasive treatments, such as mechanical ventilation, were used to prevent the irreversibility. However, extracorporeal membrane oxygenation (ECMO) was a viable alternative for eligible patients who were unresponsive to conventional treatments. Objective: This study aimed to discuss the effectiveness of the ECMO treatment during the covid-19 pandemic. Methodology: Among the studies published between 2019 and 2023 and retrieved from databases (Google Scholar, SciELO, and PubMed), 21 met the inclusion criteria. Final considerations: The ECMO treatment demonstrated potential to contribute to the recovery of patients with severe respiratory failure despite its risks and the need for a trained multidisciplinary team combined with 24-hour care and monitoring, being an alternative to inefficient conventional treatments.